Total recall [life recording software]. - Cherry, S.
This paper describes a Microsoft research initiative that focuses on memory augmentation. The research is primarily based on the MyLifeBits Project of Microsoft researcher, Gordon Bell, who, for two years, collected real life data using sensors and a still camera, called SenseCam, with the aim of developing a improved means of information retrieval. With the MyLifeBits software, the SenseCam, and the low cost of memory of all kinds, the rebirth of the PC into a personal mainframe can be realized.
Keywords: Microsoft WIndows Vista; Microsoft researchers; MyLifeBits project; SenseCam; Digital distillation; Information retrieval; Life recording software; Major software research project; Unobtrusive miniature still camera